If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34 + -1bf = 10 Solving 34 + -1bf = 10 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-34' to each side of the equation. 34 + -34 + -1bf = 10 + -34 Combine like terms: 34 + -34 = 0 0 + -1bf = 10 + -34 -1bf = 10 + -34 Combine like terms: 10 + -34 = -24 -1bf = -24 Divide each side by '-1f'. b = 24f-1 Simplifying b = 24f-1
| 5+log^3(-5*x)=9 | | lx+9l=9 | | 14m=20 | | -22=-11(x+4) | | -a-5/2a=35/4 | | 34-be=10 | | 2x-1/3=8/4 | | -0.5n+n=1.25 | | -11(x+4)=-22 | | 3x+2y+8z=38 | | 68=5e+8 | | 8x+9.72=4x+17 | | 23=-7k-6k | | 4(12-8)+16= | | -10(s+3)=-61 | | 3x+2y+3z=38 | | -3x+16=5x-8 | | 23=7k-6k | | -4+14=13x-2-12x | | 68=5+8 | | 6(x-3)=7x-2(x+1) | | 8x-14=x-7 | | 20-5x=6x-24 | | Ln(x-3)-ln(2x)=2.4 | | y=10x+29.95 | | 3x+21=20 | | 5x+97=11x-7 | | 3x+9x+7+4=6x+17+14+x | | -7x+14y=-24 | | -3+11=17x-4-16x | | 3x+4=2(3-y)fory | | 10.69+1.55t= |